Biodiesel Synthesis of Cotton Seeds Oil (Ceibapentandra) By Chemically Transesterification Process and Ion Fragmentation of Methyl Ester - Erin Ryantin Gunawan; Siska Ayu Wulandari; Emmy Yuanita; Dedy Suhendra (ALCHEMY Jurnal Penelitian Kimia, 2014)
Fossil  fuel  is  commercial  energy  sources  in  many  communities  where  their abundance  progressively  reduced  and  the  resulting  environmental  pollution.  Biodiesel  is one alternative fuel made  from vegetable  which oils are suitable to replace the function of fossil fuels and environmentally friendly. Synthesis of biodiesel from  cotton  seeds oil  was carried  out  by  chemically  ransesterification  process.  Composition  of  methyl  esters  in biodiesel  thatwas  analyzed  by  GC-MS  are  methyl palmitate  (16.71%),  methyl  8,11-octadecadienoic (46.45 %) and  methyl linoleate (4.21  %).The highest amount of  biodiesel conversion  isat  ratio of oil and  methanol (1:1)  with  the catalyst 1% (weight  of oil).  The produced biodiesel was 93.7  %.  Chemical properties of  the produced  biodiesel meets the standard SNI 04-7182-2006 i.e.  saponification value of  120.167    mg KOH / g, acid value of 0.28 mg KOH / g and iod value 55.84g iod/100g of sample.